A contrariant observation on assumed rising property values and value capture. (2nd September 2021) - Sheehan, John; Kelly, Andrew H.; Lai, Pi-Ying; Rayner, Ken
ABSTRACT: The assessment of rising property values and the resultant urge to capture some, if not most, of the presumed unearned increment in values has always exposed land use planners and legislators to an arguably flawed but longstanding premise. After reviewing key salient literary and legal aspects, the paper provides empirical material from Australia derived from British common law, and Taiwan derived from civil law. The underlying flaw is revealed in the premise that increased development potential through zoning necessarily directly or indirectly results in rising property values. The authors also posit there is an absence of methodological discourse between property rights holders, land use planners and legislators on value capture. Furthermore, there are the justifiable expectations of the community regarding rising property values and subsequent value capture to fund the provision of major infrastructure such as roads and railways. While commentators on both sides of the debate seek a transparent set of value capture outcomes to establish precedents for the future, the likelihood of such attempts being questionable. To attempt a solution without dealing with all of these intertwining issues is to risk perpetuating the disconnect between good and well understood planning law and professional practice.